LPG Direct Synthesis from Syngas over a Cu/ZnO/ZrO2/Al2O3@H‐β Zeolite Capsule Catalyst Prepared by a Facile Physical Method. Issue 6 (12th February 2020) - Du, Ce; Hondo, Emmerson; Gapu Chizema, Linet; Shen, Dongming; Ma, Qingxiang; Yan, Xiao; Mo, Shuting; Lu, Peng; Tsubaki, Noritatsu
Abstract: Liquid Petroleum Gas has recently captured great attention worldwide due to the escalating demand for non‐oil eco‐friendly fuel resources. However, the catalytic synthesis process still possesses some thermodynamic and raw material conversion flaws, in addition to unfavorable occurrence of side reactions. Herein, we present an advanced core‐shell hybrid catalyst, facilely prepared by the physical coating method, promoting not only high product yield, but also effectively eliminating design limitations accrued on employing the hydrothermal synthesis technique. The designed capsule catalyst, named CZZA@H‐β‐P‐3, has Cu/ZnO/ZrO2 /Al2 O3 (CZZA) catalyst as core and H‐β zeolite as shell. CZZA@H‐β‐P‐3 capsule catalyst was then used for direct synthesis of liquefied petroleum gas from syngas. A general mixture catalyst, Mix‐CZZA−H‐β, was used for comparison under same conditions. XRD, SEM‐EDS and NH3 ‐TPD characterization techniques were utilized to probe the extrinsic/intrinsic properties of the as‐prepared catalysts. CZZA@H‐β‐P‐3 exhibited excellent activity, in comparison. At optimal conditions, CZZA@H‐β‐P‐3 increased CO conversion from 40.94 % to 54.8 %, and LPG selectivity from 17.01 % to 26.04 %. Dimethyl ether (DME) selectivity decreased to zero. The excellent catalytic activity displayed on CZZA@H‐β‐P‐3 capsule catalyst was credited to the special core‐shell structure constructed from highly synergetic materials with a confined reaction affection, which uniquely accelerated syngas conversion to LPG. Abstract : A core‐shell hybrid catalyst (CZZA@H‐β‐P‐3) was facilely prepared by the physical coating method. The excellent catalytic activity displayed by CZZA@H‐β‐P‐3 capsule catalyst was credited to the special core‐shell structure constructed from highly synergetic materials with a confined reaction affection, which uniquely accelerated syngas conversion to liquefied petroleum gas (LPG). At optimal conditions, CZZA@H‐β‐P‐3 increased CO conversion from 40.94 % to 54.8 %, and LPG selectivity from 17.01 % to 26.04 %. Dimethyl ether (DME) selectivity decreased to zero.